Applications of Algebra in Logic and Computer Science – the Past and the Future - Grygiel, Joanna (Bulletin of the Section of Logic, 2018)
We present the history of the conference Applications of Algebra in Logic and Computer Science, whose twenty-third edition will be held in March, 2019. At the end we outline some plans for the future.